A Functional Variant in SEPP1 Interacts With Plasma Selenium Concentrations on 3-Year Lipid Changes: A Prospective Cohort Study - Zhou, Li; Liang, Xiaoling; Xie, Manling; Yin, Jiawei; Huang, Yue; Li, Xiaoqin; Shan, Zhilei; Chen, Liangkai; Zhang, Yan; Luo, Cheng; Liu, Liegang (Frontiers in Nutrition, 2021)
Background: Excess selenium has been related with adverse lipid levels in previous epidemiological studies. Meanwhile, a functional variant in SEPP1 (encodes selenoprotein P), namely rs7579, has been suggested to modulate lipid metabolism. However, the interactions between selenium status and rs7579 polymorphism on lipid changes remain unclear. Objective: To examine whether the associations between plasma selenium and 3-year lipid changes is modified by rs7579 polymorphism. Methods: A prospective cohort study was conducted among 1621 individuals to examine the associations between baseline plasma selenium and 3-year lipid changes, as well as the interactions between plasma selenium and rs7579 polymorphism on lipid changes. Results: The median (interquartile range) concentration of plasma selenium was 91.68 (81.55-104.92) μg/L. Higher plasma selenium was associated with adverse 3-year lipid changes. Comparing the highest to the lowest quartiles of plasma selenium concentrations, 3-year lipid changes were elevated by 8.25% (95% CI: 1.54%-14.96%) for triglycerides (P = 0.016), 5.88% (3.13%-8.63%) for total cholesterol (P < 0.001), 7.37% (3.07%-11.67%) for low-density lipoprotein cholesterol (P = 0.0008), 6.44% (2.66%-10.21%) for non-high-density lipoprotein cholesterol (P = 0.0009), 4.99% (0.62%-9.36%) for total cholesterol/high-density lipoprotein cholesterol ratio (P = 0.025), and 7.00% (1.55%-12.46%) for low-density lipoprotein cholesterol/high-density lipoprotein cholesterol ratio (P = 0.012). In analyses stratified by rs7579 genotypes, positive associations between plasma selenium concentrations and 3-year changes in triglycerides, TC, LDL-C, non-HDL-C, TC/HDL-C ratio, and LDL-C/HDL-C ratio were observed among CC genotype carriers, but negative associations between plasma selenium and TC/HDL-C ratio, and LDL-C/HDL-C ratio were observed among TT genotype carriers. Conclusions: Our findings suggested that plasma selenium was associated with 3-year lipid changes differentially by rs7579 genotypes, and higher plasma selenium was associated with adverse lipid changes among rs7579 CC genotype carriers, but not among T allele carriers.